Development of power factor meter using Arduino - Gunawan, Teddy Surya; Anuar, Muhammad Hadzir; Kartiwi, Mira; Janin, Zuriati (Institute of Electrical and Electronics Engineers Inc., 2018)
Nowadays, electricity is the most important or basic needs of human life. In this paper, the development of power factor meter using Arduino will be discussed. To measure power, several parameters were extracted, including voltage and current from the alternating current (AC) source. Voltage and current sensors outputs were interfaced to Arduino, in which the real power and apparent power were calculated to determine the power factor. Experimental results on the current measurement calibration showed the accuracy of our proposed power factor meter. Moreover, the measured data points were logged in an SD card, at the same time it was sent to Matlab with graphical user interface (GUI) for ease of further monitoring. Finally, IoT framework analysis for smart meter was further discussed in this paper.